PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN REKTORAT UNIVERSITAS KRISNADWIPAYANA - Wulandari Shindu Cahya; Hery Wihasnanto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The purpose of this study is to determine the effect of good Work Motivation and Work Environment for Employee Performance at Rektorat Krisnadwipayana University. This research was conducted with 55 respondents from krisnadwipayana university’s employees. Obtaining data using a questionnaire with a semantic differential scale. The results of study conducted with semantic differential scale, shows that work motivation and work environment simultaneously have asignificant influence on employee’s performance and the result is accordance with the questionnaires that have been distributed to respondents